Customer Loyalty in The Restaurant Business Sector: Analyzed Through Multidimensional Customer Equity - Wufron; Ratih Hurriyati; Puspo Dewi Dirgantari (Yayasan Sinergi Kawula Muda, 2026)
This study examines the effects of Value Equity, Brand Equity, Relationship Equity, and Financial Equity as a novel extension of the customer equity framework on Customer Loyalty in the restaurant sector in Garut Regency. The study employs a quantitative survey-based approach using Structural Equation Model Partial Least Square, with data collected from 100 restaurant customers selected through purposive sampling. The findings reveal that Brand Equity and Relationship Equity have a positive and significant influence on Customer Loyalty, whereas Value Equity and Financial Equity show positive but insignificant effects. The insignificance of Value and Financial Equity may reflect contextual factors, such as relational-oriented consumer behavior and limited sensitivity to financial considerations in local restaurant choices. The results confirm the multidimensional nature of Customer Equity and highlight the dominant role of Brand and Relationship Equity in fostering loyalty. The inclusion of Financial Equity provides a theoretical contribution by extending the customer equity model in the context of MSMEs in a developing region.